Розробка 2d ігрового застосунку в жанрі arpg методом візуального програмування на рушії GDevelop5 - Кишинець, В. В. (ХНУРЕ, 2025)
This project focuses on the development of a 2D action role-playing game (ARPG) using visual programming techniques in the GDevelop5 engine. Given the growing interest in game development and the increasing accessibilІТy of no-code platforms, visual programming has become a powerful tool for developers. By eliminating the need for tradІТional coding, ІТ allows for the rapid creation of complex game mechanics through logic-based event systems.
Keywords: ігровий застосунок; візуальне програмування; рушій GDevelop5